2022
DOI: 10.3389/fendo.2022.1091147
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance, autophagy and apoptosis in patients with polycystic ovary syndrome: Association with PI3K signaling pathway

Abstract: Polycystic ovary syndrome (PCOS) is a disease in which endocrine metabolic abnormalities coexist with reproductive system abnormalities, with the main clinical manifestations including abnormal menstruation, hirsutism, acne, infertility, and obesity, and it is also a high risk for the development of many pregnancy complications, gynecological malignancies and other diseases. Therefore, timely intervention to prevent the progression of PCOS is of great significance for improving the quality of life of most fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 85 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…In addition, testosterone was applied in GCs (Cao et al, 2022) to construct a cellular model of PCOS and transfection of CPEB1 in GCs was carried out for a deeper molecular mechanism study of PCOS in vitro. In recent years, studies have shown that apoptosis and autophagy of ovarian GCs are related to the pathophysiology of PCOS (Tong et al, 2022). Apoptosis is the F I G U R E 8 CPEB1 promotes autophagy in GCs with testosterone incubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, testosterone was applied in GCs (Cao et al, 2022) to construct a cellular model of PCOS and transfection of CPEB1 in GCs was carried out for a deeper molecular mechanism study of PCOS in vitro. In recent years, studies have shown that apoptosis and autophagy of ovarian GCs are related to the pathophysiology of PCOS (Tong et al, 2022). Apoptosis is the F I G U R E 8 CPEB1 promotes autophagy in GCs with testosterone incubation.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of autophagy and apoptosis is the key to orderly cell renewal and homeostasis (D'Arcy, 2019; Tong et al, 2022). In our study, dehydroepiandrosterone (DHEA)‐induced PCOS rats and testosterone co‐incubated GCs were performed to simulate PCOS in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, understanding the types and specific pathways of cell death involved in follicular development has been an emerging topic. Multiple studies have observed increased programmed cell death (including apoptosis and autophagy) in the ovaries from women with PCOS or PCOS animal models ( Matsuda et al , 2012 ; Li et al , 2019 ; Liu et al , 2020 ; Wang et al , 2020 ; Tong et al , 2022 ; Stringer et al , 2023 ). Similar to previous studies, our findings reveal that ferroptosis, a recently identified programmed cell death characterized by Fe 2+ -dependent phospholipid peroxidation ( Dixon et al , 2012 ; Mou et al , 2019 ), was also excessive in ovaries from women with PCOS ( Figs 1 and 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various growth factors and signalling complexes can activate PI3K, upregulating its expression and subsequently initiating downstream reactions. These reactions can be regulated by inhibiting pro-apoptotic proteins or signals generated by transcription factors [22,[49][50][51][52][53][54][55][56][57]. As a signalling molecule, Ca 2+ not only in uences the expression of apoptotic proteins but also re ect the association between this pathway and TRPC6 by detecting the protein expression of PI3K/Akt/mTOR.…”
Section: Trpc6 In Skeletal Muscle Aggravates Iri Damages Skeletal Mus...mentioning
confidence: 99%